2002
DOI: 10.1042/0264-6021:3620749
|View full text |Cite
|
Sign up to set email alerts
|

A cytochrome c mutant with high electron transfer and antioxidant activities but devoid of apoptogenic effect

Abstract: A cytochrome c mutant lacking apoptogenic function but competent in electron transfer and antioxidant activities has been constructed. To this end, mutant species of horse and yeast cytochromes c with substitutions in the N-terminal alpha-helix or position 72 were obtained. It was found that yeast cytochrome c was much less effective than the horse protein in activating respiration of rat liver mitoplasts deficient in endogenous cytochrome c as well as in inhibition of H(2)O(2) production by the initial segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Characterization of interaction between the respective anion and the designed scaffold for the anion recognition based on the naturally occurring ‘C α NN’ motif segment clearly emphasizes that the interaction is quite localized only at the main chain of the designed anion recognition scaffold segment (for DS1: Gly2‐Lys3‐Ser4; DS2: Gly2‐Gly3‐Ser4; DS3: Ser2‐Lys3‐Ser4 and DS4: Ser2‐Gly3‐Ser4), although there appear a number of Lys residues with suitable side‐chain group ( NH3+) for ionic interaction across the anchoring helix (Figure ). On a closer look one can assign that in each and every interaction irrespective of the anion or the anion recognition scaffold two out of the four oxygen atoms of the anion (sulfate/phosphate) simultaneously interact with the main‐chain C α H, NH, and NH atoms of the respective three consecutive residues of the designed sequence (Figure ), as observed for the crystal structures having the naturally occurring ‘C α NN’ motif [1MUG: residues 107–110; 1YCC: residues 1–4; 1JW9: residues 39–42 and several others] as depicted by Denessiouk et al It is also observed that in each set of the respective 250 docked conformers, out of these two interacting oxygen atoms, one oxygen atom is interacting concurrently with the C α H atom of the i −1th residue and the main chain NH atom of the i th residue; while the other interacting oxygen atom interacts only to the main‐chain NH atom of the i + 1th residue through hydrogen bond (Figure ). This is similar to the reported crystal structures as well as the naturally occurring ‘C α NN’ motif containing context free peptides …”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Characterization of interaction between the respective anion and the designed scaffold for the anion recognition based on the naturally occurring ‘C α NN’ motif segment clearly emphasizes that the interaction is quite localized only at the main chain of the designed anion recognition scaffold segment (for DS1: Gly2‐Lys3‐Ser4; DS2: Gly2‐Gly3‐Ser4; DS3: Ser2‐Lys3‐Ser4 and DS4: Ser2‐Gly3‐Ser4), although there appear a number of Lys residues with suitable side‐chain group ( NH3+) for ionic interaction across the anchoring helix (Figure ). On a closer look one can assign that in each and every interaction irrespective of the anion or the anion recognition scaffold two out of the four oxygen atoms of the anion (sulfate/phosphate) simultaneously interact with the main‐chain C α H, NH, and NH atoms of the respective three consecutive residues of the designed sequence (Figure ), as observed for the crystal structures having the naturally occurring ‘C α NN’ motif [1MUG: residues 107–110; 1YCC: residues 1–4; 1JW9: residues 39–42 and several others] as depicted by Denessiouk et al It is also observed that in each set of the respective 250 docked conformers, out of these two interacting oxygen atoms, one oxygen atom is interacting concurrently with the C α H atom of the i −1th residue and the main chain NH atom of the i th residue; while the other interacting oxygen atom interacts only to the main‐chain NH atom of the i + 1th residue through hydrogen bond (Figure ). This is similar to the reported crystal structures as well as the naturally occurring ‘C α NN’ motif containing context free peptides …”
Section: Resultsmentioning
confidence: 81%
“…It has been found that among several anion‐recognizing motifs the ‘novel phosphate binding ‘C α NN’ motif’ is different from [Gly/Ser/Thr/Ala‐Gly‐[Gly/Ala] or ‘structural P‐loop’ [(Gly‐Xxx‐Xxx‐Xxx‐Xxx‐Gly‐Lys‐(Ser, Thr)] or ‘nest’ . Unlike other motifs, where the interaction with anion is mediated either via the positively charged side chains and/or via the main chain amides of the anion recognition motif of proteins; participation of the three main chain atoms ( Ciα −1 , N i , N i +1 ) of the structurally invariant three consecutive residues at the functional interface and especially the Ciα −1 atom in mediating anion‐protein interaction makes the ‘C α NN’ motif unique among the existing other anion binding motifs. It is found that in several occasions this ‘C α NN’ motif having conserved GXX ([Gly/Ser]‐Xaa‐[Thr/Ser]) sequence motif with right handed βαα or βαβ conformation recognizes sulfate ion in lieu of the phosphate ion during crystallization .…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between Apaf-1 and cyt c is thought to be predominantly electrostatic, involving surface lysine residues and the solvent-exposed pyrrole ring C of cyt c [10-15]. It has also been reported that during apoptosis cyt c undergoes a conformational change, which may be required for binding to Apaf-1 [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…‘C α NN’ [13], ‘nests’ [14][16], ‘structural P-loop’ [17], ‘cup’ [18] along with motifs for recognizing adenine, adenine-containing nucleotides and its analogues [12], [19], [20]], the recently identified ‘C α NN’ motif [13], common to more than 100 fold-representative protein structures as observed in the FSSP database, has a specially characteristic feature. This motif consists of main chain atoms of three consecutive residues (C α −1 N 0 , N +1 ), often present in the active sites of proteins and participates directly in several key regulating functions [1]–[3], [21].…”
Section: Introductionmentioning
confidence: 99%